Intoxication Of Mercury: Risk Factors, Pathophysiology And Its Impact For Pregnant Women In The Artisanal And Small Scale Gold Mining - Ekawanti, Ardiana; Priyambodo, Seto (Faculty of Medicine Universitas Mataram, 2020)
Mercury exposure of pregnant women comes from various sources including pollution from gold mining, from the consumption of fish and equipment in the neighborhood where they live. Intoxication that occurs as a result of exposure is determined by the type of mercury, route, dose, duration of exposure and age of the host. Mercury exposure in a pregnant woman not only causes intoxication for her but also affects the fetus . The fetus is a developmental phase that is very susceptible to mercury exposure of all kinds from its mother. Various effects that can arise from this exposure on the fetus include stillbirth, low birth weight and congenital abnormalities.